Radiomics, metabolic, and molecular MRI for brain tumors - Vollmuth, Philipp; Andronesi, Ovidiu-Cristian (Seminars in neurology, 2018)
Magnetic resonance imaging plays a key role in diagnosis and treatment monitoring of brain tumors. Novel imaging techniques that specifically interrogate aspects of underlying tumor biology and biochemical pathways have great potential in neuro-oncology. This review focuses on the emerging role of 2-hydroxyglutarate-targeted magnetic resonance spectroscopy, as well as radiomics and radiogenomics in establishing diagnosis for isocitrate dehydrogenase mutant gliomas, and for monitoring treatment response and predicting prognosis of this group of brain tumor patients.